A primazia institucional no mundo e modelos de crescimento: revisitando a teoria institucional de Dani Rodrik - Dolci, Renato de Carvalho (2015)
From the study of empirical analysis based on article Institutions Rule: the Primacy of Institutions over Geography and Integration in Economic Development (2002) Dani Rodrik, Arvind Subramanian and Francesco Trebbi, this study seeks to empirically estimate more compliant institutional estimators with assistance from other indicators, classifying institutional estimators in four axes (legal, political, economic and social) and testing them on the model developed by the authors cited above. The result shows preponderance of legal apparatus in the adherence of institutional variable, excluding the economic quality (potential problems of reverse causality) and shows that more general variables such as force of law and government effectiveness have better performance than estimators very focused on institutionalities specific, such as political stability and governance system adopted by the country